Hubungan Struktur Pasar dan Perilaku Pasar Serta Pengaruhnya Terhadap Kinerja Pasar - P. Eko Prasetyo (Economic Journal of Emerging Markets, 2009)
The objective of this research are to analyze the model of the correlation between mar¬ket structure and market conduct and their effects on the market performance. This re¬search was conducted by using the survey method on 112 households of respondent samples of bamboo crafts makers from 625 household population bamboo craft makers in Bantul subdistrict, the Province of Special District of Yogyakarta. The sampling technique used in this research is two steps of cluster random sampling technique, and the analysis models used are the industrial organization and simultant system regression-correlation model.